Pengaruh Pemberian Metode Simulasi Siaga Bencana Gempa Bumi terhadap Kesiapsiagaan Anak di Yogyakarta - Indriasari, Fika Nur (Jurusan Keperawatan FIKES UNSOED, 2016)
Indonesia is located within the ring of fire and Yogyakarta is one of the area which is experiencing with earthquake. The earthquake happened in 2006 left many victims. Most of them are elderly and children. Not all children are trained to deal with disaster, therefore it is necessary to conduct a training to elementary school so the children have a knowledge how to deal with this disaster if it is suddenly happened. The main aims of this research is to find out the effect of disaster simulation method toward the children readiness, ability and involvement of children in doing simulation, the children preparedness before and after receiving the training. Method. The research design applies quasi experiment with one pre post test design. The sample are taken by using purposive sample for 31 respondents and the data are collected by using questioners and observation checklists. The hypothesis is tested by using Wilcoxon test. Results of this study showed there is influence on the preparedness of disaster simulation method children with a value of p 0.001, all the children capable and involved after performing the simulation as many of 5 times while the child preparedness before the simulation in the category of less ready as numberÃ‚Â of 22 children (71%) and after simulation increased to 23 children (74.2%). Conclusion. The training of awareness and readiness to face an earthquake disaster increase the level of children awareness. All of the level 6 Giwangan elementary students is able and involved after the training was repeated 5 times and most of the children showed that the level of awareness is categorised as less ready.